THE SOCIOLOGY OF KNOWLEDGE: A Preliminary Analysis on The Sociological Approach to The Development of Islamic Religious ScÄ±ences - Latief, Mohamad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This paper attempts to descriptively explore the exposition on the sociology of knowledge as a new branch of sociology. This description aims at proposing the basic understanding of the nature of the discipline and further introducing its possible application for the rejuvenation of Islamic religious sciences. It is due to the fact, however debatable, that these sciences are sometimes discerned so rigid, absolute, and unproductive; so that the application of the method becomes inevitable. Within this context of applying the sociology of knowledge to develop Islamic religious sciences, the paper critically discloses fallacy in that the method generates ideological premises of pluralism, relativism, and liberalism. The demanding application thus poses intellectual challenges against the Muslim community.